Utilization of English in Community Social Interaction in the Tourism Area of Berastagi Regency North Sumatra - Sibarani, Choms Gary Ganda Tua; Hidayat, Nasrullah; Ahsan, Jabal (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Tourism plays a crucial role in contributing to Indonesia's economy. The use of English in tourist destinations is vital, including in North Sumatra's tourism sector. Berastagi is a well-known tourist destination in North Sumatra, attracting many international visitors. It is important for all tourism stakeholders in Berastagi to be proficient in foreign languages to effectively engage with foreign tourists. As such, tourism professionals must have clear objectives to reduce the potential negative effects of national and regional tourism development on local communities, especially in terms of foreign language use. This study employs a descriptive qualitative approach. The findings reveal that foreign languages are essential in business activities within Berastagi's tourism area, significantly boosting sales and benefiting business operators. Additionally, the use of foreign languages enhances social interactions with foreign tourists visiting the city.